Learning Management Based on Akita Approach on Multiplication and Division for Grade 3 Students - Piyaphat Thiangtrong; Jiraporn Chano; Bussayarat Nithideechaiwarachok (Journal of Educational Issues, 2024)
The Akita approach is the guideline in learning that responds to rapid changes in the 21st century. This research aimed to determine the effectiveness of learning management based on the Akita approach in accordance with the criteria efficiency of 75/75 and to explore the index of effectiveness of learning management pursuant to the Akita approach. Furthermore, to discover students’ learning retention and to study the students’ satisfaction with learning management based on the Akita approach. The participants were 34 primary school students in the northeast of Thailand, selected by cluster random sampling. Research instruments comprised of learning management plans, achievement tests, and a questionnaire. Statistics were used, including percentage, mean and standard deviation, and dependent samples t-test. The results found that, firstly, learning management plans based on the Akita approach identified students’ efficiency (E1/E2) at 86.46/85.29, which was higher than the specified criteria. Secondly, the index of effectiveness of the learning management plans based on the Akita approach on multiplication and division of students was equal to 0.6835 or 68.35 percent. Thirdly, for students who studied by using Akita-based learning management plans on multiplication and division topics, the post-test scores after studying and the post-test scores after they had finished studying for two weeks appeared to reveal no difference, which showed the persistence of students in learning. Lastly, students were satisfied with studying multiplication and division by Akita-based learning management plans with high overall scores and each item at the highest (x̅ = 4.65-4.88) level.